How has the Self-Perceived Health Shaped the COVID-19 Causalities in the Visegrad Countries? - Ibrahim Niftiyev; Rena Huseynova (Scientific Collection InterConf+: Proceedings of the 3th International Scientific and Practical Conference «Theory and Practice of Science: Key Aspects», Rome, Italy, May 21-22, 2021, 2021)
Similar to many countries around the world, Visegrad countries (Poland, Czech Republic, Slovakia, and Hungary) have been hit hard by the COVID-19 pandemic after the second half of 2020. The outbreak was handled with both success and challenges, experiencing severe declines in economic activities. Despite a complex set of factors determining how the countries handled the pandemic in the hospitals, having a look for the period before the pandemic to analyze what were the change patterns among the citizens concerning the healthcare system poses an interesting analytical way to compare with the COVID-19 trends. By utilizing the Eurostat data on the self-perceiving health conditions, the graphical analysis of this paper suggests that Visegrad countries shared similar trends and dynamics in COVID-19 infection causalities, and also pre-pandemic health situations. Furthermore, the results of the calculated linear and exponential slopes of the infected and death cases identified that the countries with higher averages of self-perceived states have less steep functional reflections.
Keywords: 330; COVID-19; Visegrad countries; self-perceived health